A relação entre Brasil e Israel no governo Bolsonaro: Impactos do discurso religioso evangélico na condução da política externa brasileira. - Herrmann, Leonardo Brito (2023)
The growing presence of religion, specifically evangelical Christianity, in Brazilian politics has raised important questions about its impacts on the formulation of public policies. However, this influence appears to have spilled over from its traditional stage of domestic political discussions to the more rarified realm of foreign policy production. The present work seeks to analyze whether, and in what way, ideas about the State of Israel, present in the Brazilian Pentecostal milieu, influenced Brazil's foreign policy during the Bolsonaro government. After a methodological introduction that details the computational process of content analysis of Bolsonaro's speeches and Gustavsson's model (1999) for the analysis of foreign policy changes, the paper provides a preliminary survey on religion as a subject of study in International Relations, and analyzes the evangelical movement in Brazil, its denominational subdivisions, main beliefs, demographic evolution, and the role of Israel in the theology of these groups. Next, a brief history of the relationship between Brazil and Israel from the first Lula government to Temer's government is presented, aiming to establish some of the main guidelines that oriented this interaction from 2003 to 2022. The involvement of Jair Bolsonaro, from Congressman to President, with the State of Israel and his approach to the evangelical segment are then analyzed. Part of this analysis was based on Bolsonaro's discursive corpus throughout his presidency, using computational tools to present some relationships between different keywords in his vocabulary. Through this study, the importance of the evangelical segment was established as an element capable of influencing - through political pressures and leaders close to the presidency - the conduct of national foreign policy, with a visible impact of their ideas on the president's speeches and decision-making process, although in a less ambitious way than desired by some of its leaders.